STRESS E REAJUSTAMENTO SOCIAL EM AUXILIARES DE ENFERMAGEM - Mogentale, Ani Paula (2011)
The purpose of the present study was to find out the social-demographic and cultural profile of nursing assistants, to evaluate the level and presence of symptoms of stress, to evaluate and describe the social readjustment and to determine relation among variables related to work and stress. 126 nursing assistants who attended a technical course in nursing participated of this study. Making use of the following instruments: a) the social-demographic and cultural questionnaire; b) Scale of Social Readjustment of Holmes-Rahe and c) Inventory of Lipp Symptoms of Stress. Data were obtained in classrooms of three technical schools of the greater São Paulo and these data were treated statistically by tests X ² and r Person for the relations among variables, with the support of the program SPSS version 17. The results indicated a predominance of a female person, married, with minimum age of 19 years old and maximum of 56 years old and Catholics and Evangelicals religious. Of which (79%) worked in one job only, with a 5-year professional experience and the sector with most professionals was home care . As for the working hours, the majority of the professionals worked in Day-time shift, and studied at night-time schools. As for stress, 57.9% presented a certain level of stress, 41.3% was in the resistance phase and 37.3% indicated stress of psychological nature. As for social readjustment, most of the nursing assistants, which corresponded to 48.4%, was within the average, with reasonable chances of becoming sick, that is, presented regular capacity for adaptation to the new and unknown events that occur during life. The results indicate that the professionals who presented significant level of stress obtained figure higher (average) on the social readjustment scale, compared to the professionals who did no present stress, indicating that these individuals had more probability of being sick or becoming sick.